Guidelines of the Polish Ophthalmological Society on refractive lens exchange - Szaflik, Jacek P.; Izdebska, Justyna; Grabska-Liberek, Iwona; Kałużny, Bartłomiej; Lubiński, Wojciech; Mrukwa-Kominek, Ewa; Muzyka-Woźniak, Maria; Staniewicz, Jan (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
The article contains recommendations of the Polish Ophthalmological Society on refractive lens exchange, a technique of surgical correction of refractvie error in patients who do not qualify for other refractive procedures (such as: LASIK, PRK or ICL phakic lens implantation) as well as those who want to avoid the visual consequences of presbyopia by implanting an appropriate intraocular lens (e.g. multifocal or extended depth of focus).